Strategy to Strengthen Halal Tourism - Octavia, Azella Nosih; Suliswanto, Muhammad Sri Wahyudi; Firmansyah, Muhammad (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
Java Province has many natural tourist attractions, especially in Trenggalek Regency. In Indonesia, the development of tourism with a halal concept is becoming a trend. Several tourist attractions are competing to create or change their tourist attractions into halal tourism so that Muslim tourists who come to visit feel safer. This study aimed to determine the critical aspects of developing halal tourism in Trenggalek Regency. This research method is qualitative, using SWOT analysis. The results of this study indicate that the potential for natural beauty in Trenggalek Regency is an aspect that can positively impact the strengthening of halal tourism and increase regional income because of the many existing opportunities. Strengthening halal tourism in Trenggalek Regency is in quadrant 1, namely in the strengths and weaknesses (SO) strategy, so that strategies to increase visitor attraction can be carried out by improving the quality of tourism by utilizing existing opportunities. Overall, this study provides a strategic framework for the development of halal tourism in Trenggalek Regency, which has broad implications for economic growth, cultural expansion, infrastructure development, stakeholder collaboration, and policy planning.